Cultivation of Pakcoy (Brassica rapa subsp. Chinensis) Using Hydroponics and Its In Situ Utilization for Consumption: Budidaya Pakcoy (Brassica rapa subsp. Chinensis) Sistem Hidroponik dan Pemanfaatannya Secara In Situ Untuk Konsumsi - Septabrina, Canda Kharisma; Sutarman (Procedia of Engineering and Life Science, 2025)
This study aimed to analyze the cultivation process of pakcoy (Brassica rapa subsp. Chinensis) using the Nutrient Film Technique (NFT) hydroponic system, focusing on the effects of nutrient concentration variations on plant growth and quality, as well as its in situ utilization to ensure food safety and nutritional value. The experiment was conducted for 24 days with three nutrient concentration treatments. Observed parameters included plant height, leaf number, fresh weight, vitamin C content, and antioxidant activity. The results revealed that nutrient concentration significantly affected vegetative growth and crop quality. Optimal growth occurred at an electrical conductivity (EC) range of 1.5–2.0 mS/cm, producing an average plant height of 18.5 cm, fresh weight of 110 g, vitamin C content of 42 mg/100 g fresh weight, and antioxidant activity of 55%. Both low and high nutrient levels decreased nutrient uptake efficiency due to ionic stress. In situ utilization of harvested crops resulted in a 5–10% reduction in vitamin C and a 3–8% reduction in antioxidant activity, yet the nutritional quality remained acceptable for fresh consumption. Overall, the NFT hydroponic system proved effective in enhancing growth performance, water efficiency, and nutritional quality of pakcoy, making it suitable for sustainable urban agriculture applications.